COVID-19 pandemic: the insights on online learning / Ramli Saad ... [et al.] - Saad, Ramli; Ali Akbar, Yong Azrina; Mahshar, Mursyda (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
COVID-19 pandemic has changing most of normal things including the higher education system which is changing from face-to-face class to the online learning. Higher education institution's operation is one of the affected sectors due to the COVID-19 pandemic that spread all around the world. Majority of universities and colleges have revised their courses to suit with a fully remote online learning approach. Their focus during that time is merely more towards survival than daily growing success (Woods, 2020). Thus, students and educators face difficulties to adapt with the new norm and new systems that already had been changed. Ensuring digital accessibility is critical, during this difficult time. Not every educator or student has access to all or any digital devices, the internet, or Wi-Fi. Due to a lack of suitable digital tools, no internet connections, or unreliable Wi-Fi connections, some students may miss out on valuable learning possibilities (Woods, 2020). Students from lower and middle socioeconomic strata not only have problem to access good quality internet service and good learning equipment and devices, but also have limited learning space at home and online learning resources (Barrot, Llenares, & del Rosario, 2021). The fact that higher education institutions, government, policy makers and internet companies' provider play a vital role in the success of online learning. Proactive strategies must be implemented in order to reduce the difficulties faced by educators and students.